MARKET PRICING SYSTEM OF CERTIFIED FOOD SEEDS IN ACEH ACCORDING TO THE CONCEPT OF TSAMAN - Putri Balqis; Teuku Surya Reza (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
Abstract This study aims to analyse the market mechanism of certified food crop seeds, particularly rice seeds, in Aceh Besar Regency. It also evaluates the pricing system through the concept of tsaman within the framework of Islamic economics and based on the Regulation of the Minister of Agriculture of the Republic of Indonesia Number 12 of 2018 concerning the production, certification, and distribution of seeds. The background of this study is motivated by the phenomenon of certified seed prices that tend to be high, yet lack transparency and a clear pricing basis, resulting in injustice for farmers, especially those from low-income groups. This research employs a descriptive qualitative approach, utilizing primary data collected through in-depth interviews with representatives from Aceh UPTD BPSBTPHP, farmers, and agricultural input suppliers, as well as secondary data from relevant literature and regulatory documents. The findings reveal that the absence of explicit pricing provisions in MOA No. 12/2018, along with limited dissemination, results in non-transparent pricing that is difficult for farmers to access. From the perspective of tsaman, this condition does not reflect the principles of fairness, openness, and price appropriateness. Consequently, some farmers prefer to use uncertified seeds obtained through mutual exchange among fellow farmers. This study recommends a pricing policy that is transparent, adaptive to market conditions, and aligned with Sharia principles to support the development of a healthy, fair, and sustainable seed market system.